2009
DOI: 10.1164/rccm.200811-1678oc
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Angiotensin-converting Enzyme 2 as a Therapeutic Target for the Prevention of Pulmonary Hypertension

Abstract: Rationale: It has been proposed that an activated renin angiotensin system (RAS) causes an imbalance between the vasoconstrictive and vasodilator mechanisms involving the pulmonary circulation leading to the development of pulmonary hypertension (PH). Recent studies have indicated that angiotensin-converting enzyme 2 (ACE2), a member of the vasoprotective axis of the RAS, plays a regulatory role in lung pathophysiology, including pulmonary fibrosis and acute lung disease. Based on these observations, we propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
222
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(238 citation statements)
references
References 30 publications
14
222
2
Order By: Relevance
“…This hypothesis is supported by recent data (18). Although neither Ang II nor Ang-(1-7) levels in the thrombi were determined in the present investigation, a large number of studies have shown that Ang II is a prothrombotic agent (19,20).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This hypothesis is supported by recent data (18). Although neither Ang II nor Ang-(1-7) levels in the thrombi were determined in the present investigation, a large number of studies have shown that Ang II is a prothrombotic agent (19,20).…”
Section: Discussionsupporting
confidence: 78%
“…Unfortunately, no Mas antagonists were used in the present study. However, an experimental model of pulmonary hypertension demonstrated that the protective effects evoked by XNT were completely abolished by the coadministration of A-779 (18). This important finding should be taken into consideration in future experiments.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Consequently, it decreases blood pressure, improves cardiac function and decreases renal fibrosis in SHR [142] . It also has antihypertensive effects in rats with pulmonary hypertension [143] . These results together suggest that, besides inhibition of renin and ACE, associated or not with the blocking of AT1 receptor, activation of the ACE2/Ang-(1-7)/Mas axis and its protective effects is emerging as an excellent alternative therapy for the treatment of hypertension and cardiovascular diseases.…”
Section: New Targets For Hypertension Treatmentmentioning
confidence: 99%
“…47 Other potential therapies currently being investigated include PPRgamma agonists, angiotensin converting enzyme 2, selective serotonin receptor inhibitors, vasoactive intestinal peptide, soluble glucocorticoid stimulators, tetrahydrobiopterin, aspirin, statins, and serine protease inhibitors. 20,[48][49][50][51][52][53][54] Sex hormone manipulation is another potential therapeutic target given the female predominance in PAH. 55 Finally, since right ventricular function is the primary determinant of survival in PAH, future therapies may directly target the right ventricle.…”
mentioning
confidence: 99%